Research progress of targeted therapy regulating Th17/Treg balance in bone immune diseases - Wang, Xiaxia; Sun, Bai; Wang, Yujie; Gao, Peng; Song, Jiayi; Chang, Weirong; Xiao, Zhipan; Xi, Yongbin; Li, Zhonghong; An, Fangyu; Yan, Chunlu (Frontiers in Immunology, 2024)
Rheumatoid arthritis (RA) and postmenopausal osteoporosis (PMOP) are common bone-immune diseases. The imbalance between helper (Th17) and regulatory T cells (Tregs) produced during differentiation of CD4+ T cells plays a key regulatory role in bone remodelling disorders in RA and PMOP. However, the specific regulatory mechanism of this imbalance in bone remodelling in RA and PMOP has not been clarified. Identifying the regulatory mechanism underlying the Th17/Treg imbalance in RA and PMOP during bone remodelling represents a key factor in the research and development of new drugs for bone immune diseases. In this review, the potential roles of Th17, Treg, and Th17/Treg imbalance in regulating bone remodelling in RA and PMOP have been summarised, and the potential mechanisms by which probiotics, traditional Chinese medicine compounds, and monomers maintain bone remodelling by regulating the Th17/Treg balance are expounded. The maintenance of Th17/Treg balance could be considered as an therapeutic alternative for the treatment of RA and PMOP. This study also summarizes the advantages and disadvantages of conventional treatments and the quality of life and rehabilitation of patients with RA and PMOP. The findings presented her will provide a better understanding of the close relationship between bone immunity and bone remodelling in chronic bone diseases and new ideas for future research, prevention, and treatment of bone immune diseases.